The skin map - Lawhead, Stephen R., 1950- (Lawhead, Stephen R., 1950- Bright Empires novel, 2010)
When Kit Livingstone learns that Britain's "ley lines" are not legends but pathways to other worlds, he's determined to find a map tattooed on a piece of skin in order to travel to the dangerous realms. But are the intricate codes more than they seem--can they really begin a quest to regain paradise?